Hukum Investasi Aset Digital Dalam Perspektif Fikih Islam: Analisis Fatwa DSN-MUI No. 116/DSN-MUI/IX/2017 - Syahfitri, Annisa Aulia; Lathifa, Liyyu; Ikhlasul Amal Wishri; Taufik Hidayat (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
This research (2023-2024) analyzes the compatibility of digital asset investments with Islamic fiqh principles in Indonesia. Digital asset investments include cryptocurrency, a digital currency for investment, NFTs, digital collections, DeFi, a financial system without intermediaries, metaverse, a virtual world that combines digital assets, and asset tokenization, which converts real assets into digital ones. All these concepts utilize blockchain technology but have different mechanisms and objectives. This research aims to analyze the legality and compatibility of digital asset investments with Islamic law in Indonesia. The findings indicate that digital assets can be accepted as investments compliant with shariah if conducted with clear contracts and without elements of speculation, usury, or gambling. This research concludes that digital assets have great potential but must comply with Islamic shariah regulations.